Semur cendawan: Mushroom cultivation innovation for food security in Waru, East Kalimantan - Abdul Kahar; Muhammad Busyairi; Dharma Saputra; Asih Soenarih; Andita Hayuning Kurnia; Mada Marhaenesia; Muthia Andriani; Aulia Miftahul Jannah; Marista Sihombing (Universitas Muhammadiyah Magelang, 2024)
The Semur Cendawan Program was initiated in response to limited agricultural land ownership in Waru Village, Waru District, Penajam Paser Utara Regency. The program aims to shift community mindset towards sustainable agriculture, enhancing food security through intensified land use, and creating new income streams for farmers via mushroom cultivation. Implemented through training and mentorship for the Dahlia Women's Farmers Group and other farmer groups, the program has successfully improved farmers' mushroom cultivation knowledge and skills. Consequently, the community's income has increased through independent mushroom production and marketing. The program has fostered new business opportunities and inspired replication among other farming groups.